Non-steroidal anti-inflammatory drugs and myocardial infarctions: comparative systematic review of evidence from observational studies and randomised controlled trials. Issue 10 (7th March 2007) - Scott, P A; Kingsley, G H; Smith, C M; Choy, E H; Scott, D L
Abstract : Objective: The comparative risk of myocardial infarction (MI) with cyclo-oxygenase-2-specific drugs and traditional non-steroidal anti-inflammatory drugs (NSAIDs) was determined. Methods: The results of studies of a suitable size in colonic adenoma and arthritis—that had been published in English and from which crude data about MIs could be extracted—were evaluated. Medline, Embase and Cinahl (2000–2006) databases, as well as published bibliographies, were used as data sources. Systematic reviews examined MI risks in case-control and cohort studies, as well as in randomised controlled trials (RCTs). Results: 14 case-control studies (74 673 MI patients, 368 968 controls) showed no significant association of NSAIDs with MI in a random-effects model (OR 1.17; 95% CI 0.99 to 1.37) and a small risk of MI in a fixed-effects model (OR 1.32; 95% CI 1.29 to 1.35). Sensitivity analyses showed higher risks of MI in large European studies involving matched controls. Six cohort studies (387 983 patient years, 1 120 812 control years) showed no significant risk of MI with NSAIDs (RR 1.03; 95% CI 1.00 to 1.07); the risk was higher with rofecoxib (RR 1.25; 95% CI 1.17 to 1.34) but not with any other NSAIDs. Four RCTs of NSAIDs in colonic adenoma (6000 patients) showed an increased risk of MI (RR 2.68; 95% CI 1.43 to 5.01). Fourteen RCTs in arthritis (45 425 patients) showed more MIs with cyclo-oxygenase-2-specific drugs (Peto OR 1.6; 95% CI 1.1 to 2.4), but fewer serious upper gastrointestinal events (Peto OR 0.40; 95% CI 0.31 to 0.53). Conclusion: The overall risk of MI with NSAIDs and cyclo-oxygenase-2-specific drugs was small; rofecoxib showed the highest risk. There was an increased MI risk with cyclo-oxygenase-2-specific drugs compared with NSAIDs, but less serious upper gastrointestinal toxicity.